EFFECTIVENESS PRUNING AND PLANTING MEDIA ON THE MORPHOLOGY AND RESULTS OF FLOATING RED CHILIES - Aprilia, Sherina Eka; Susilawati, Susilawati; Hermawan, Agus (BIOVALENTIA: Biological Research Journal, 2023)
Horticultural commodities hold significant economic potential in Indonesia, particularly red chilies, which serve various purposes such as a spicy,traditional spicy, and industrial raw material. This research aims to assess the impact of shoot pruning and planting media composition on the morphology and yield of red chili plants. The study employed a Randomized Factorial Group Desugn (RAKF) with two main treatments : shoot pruning and planting medium composition. Results indicate that pruning shoots at 35 days after planting (P4) enhances the cultivation of red chili plants, as evidenced by improved plant height, earlier flowering, and increased root length. Furthermore, a planting medium composed of soil, cow dung compost, and 2:1:1 husk charcoal (M4) proves to be more beneficial for red chili yield, demonstrated by higher plant height, stem diameter, and root length.